Paradigma Kepastian Hukum Pembiayaan Musyarakah Pada Bank Syariah: Perspektif Hukum Positif - Rayno Dwi Adityo (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2015)
The development of syariah banking in this country bringing effort where that positive developments have been in such rapid. That thing with an assortment of products in the form of syariah banking one of them was a musyarakah. Uniquely inside musyarakah this to form tense classical fiqh still shaped very simple can be written and unwritten as well as the absence of security aspects attached to the financing patterns like this. Currently musyarakah pattern in the banking industry is poured in writing in agreement as we know it with a term of standard contract and in the product financing musyarakah is also glue aspects of colleteral. From the image we can see that product musyarakah financing in legal positive viewpoint having an aspect of legal certainty in a contract with standard contract and colleteral for security aspect.